Kaidah al-'Ām dan Aplikasinya pada Tafsīr Tahrīr Wa Tanwīr: The al-'Ām Rule and Its Application to Tafsīr Tahrīr Wa Tanwīr - Abdurrahman Ahady; Muhammad Irfan (DIRASAH: Jurnal Kajian Islam, 2025)
This study aims to explore the application of the al-’ām rule in the interpretation of the Qur'an through a study of Ibn 'Āshūr's Tafsīr Tahrīr wa Tanwīr. With a library research approach, eight main rules are analyzed to understand the application of generality in the interpretation of the Qur'an. The results show that the al-’ām rule has a significant role in compiling the principle of generality which includes linguistic, legal, and Shari'ah aspects. Ibn 'Āshūr utilized this rule to interpret verses with an in-depth linguistic approach, paying attention to munāsabah, and basing the interpretation on historical relevance. The main findings indicate that the application of the al-’ām rule enriches the understanding of tafsir, avoids errors of interpretation, and provides contextual solutions in response to the challenges of the times. In conclusion, this study emphasizes the importance of al-’ām rules as a foothold in a more systematic and universal interpretation, especially in linguistics-based tafsir and tahlīli method.